PENGUJIAN PERILAKU PREDATOR DAN ANTI-PREDATOR PADA IKAN LELE (Clarias gariepinus Burchell, 1822) TRANSGENIK F3 Testing Predator and Anti-Predator Behavior in African Catfish (Clarias gariepinus Burchell, 1822) Transgenic F3 - Putri Widyawati; Darma Bakti; Desrita Desrita; Huria Marnis (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
African catfish (Clarias gariepinus Burchell, 1822) transgenic containing Pangasius hypothalmus Growth Hormone (PhGH) has better performance compared with non-transgenic. However, before transgenic African catfish are released and utilized, their genetic impact on the natural environment must be examined. Predator avoidance is one of the major fitness traits determining potential environment risk. Transgene detection was performed using the PCR (Polymerase Chain Reaction) method and electrophoresis. Furthermore, the observation of the performance of growth including the growth of the length (the average length of the fish at the end - the average length of the fish at the beginning), the growth in weight (average weight of fish in the end – average fish at the beginning) and the survival rate (the number of fish that live in end / number of fish lived at the beginning). Results indicate that non-trangenic had better predator avoidance than transgenic African catfish. Non-transgenic has a better growth performance than transgenic African catfish and has a higher survival rate. Transgenic African catfish could be used for commercial aquaculture without affecting the natural environment because the increased susceptibility of transgenic to predators would most likely decrease or eliminate the transgenic genotype.Keywords: Clarias gariepinus, Transgenic, Environmental Risk